Studi Literatur: Penerapan Komunikasi SBAR dalam Pelaksanaan Keselamatan Pasien di Rumah Sakit (Studi di Indonesia) - Risma Ainun Shafira; Inge Dhamanti (Universitas Airlangga, 2023)
Background: In carrying out patient safety, the hospital has varied ways to maximize the implementation of patient safety, one of which is the use of effective communication as an effort to maximize the implementation of patient safety at the hospital. One of the effective communication methods is SBAR communication (Introduction, Situation, Background, Assessment, Recommendation) to achieve critical thinking skills and save time. SBAR communication used in effective communication is a system that is easy to remember amd a real mechanism used to convey a patient's condition that is critical or needs immediate attention and action. Purpose: The purpose of this study is to determine the application of effective SBAR communication in the implementation of patient safety in hospitals. Methods: The method used is to conduct literature reviews from various journals and articles related to the application of SBAR communication in hospitals and its implementation in patient safety in hospitals in Indonesia. The articles used are taken based on filtering through a database which is then filtered for titles, abstract to completeness and conformity with the research theme. Result: The results are implementation of the effective SBAR communication technique recommended by WHO has been used by most hospitals in Indonesia, although in practice there are still some things need to be fixed and managed but the implementation itself has proven to be effective and very influential on patient safety in the hospital. Conclusion: SBAR communication is an effective communication framework used in patient safety in hospitals. There are factors that influence the implementation of SBAR communication including experience, years of service of practitioner, equalization of perceptions and understanding of implementation related to SBAR techniques, socialization or debriefing related to the use of these techniques and the existence of SOPs in hospitals. In its implementation, SBAR communication is mostly considered effective and has a positive relationship with patient safety efforts.